Higher Dimensional Bianchi Type III Dark Energy Cosmological Model with Cosmic String in f(R)Theory of Gravitation - Bayaskar, S. N.; Somwanshi, K. V.; Shoeb, A. A. Q. (Journal of Scientific Research, 2026)
This study investigates higher-dimensional Bianchi type-III spacetime within the framework of f(R) gravity to derive cosmological solutions for Einstein’s field equations (EFE) incorporating dark energy and cosmic strings. To obtain a deterministic solution, we utilized specific conditions: a power-law relationship between F and the average scale factor, a proportionality between the shear and expansion scalars, and a functional link between the Hubble parameter and the average scale factor. We investigated both exponential and power-law expansion models. Furthermore, the temporal evolution of the relevant physical parameters is analysed and illustrated graphically.